Family associations of coronary heart disease risk factors in adolescents - D. V. Denisova; S. V. Burakova; L. G. Zavyalova (Кардиоваскулярная терапия и профилактика)
Aim. To investigate prevalence and family associations of traditional coronary heart disease (CHD) risk factors (RF) in adolescents aged 14‑17 years and their parents. Material and methods. Four population surveys of 14‑17‑year‑old adolescents have been performed. In total, 2569 individuals were examined (1214 boys and 1355 girls). The examination included: questionnaire survey, double blood pressure (BP) measurement, anthropometry, biochemical blood assay (total cholesterol, TCH; high‑density lipoprotein CH, HDL‑CH; triglycerides, TG). The participants' parents took part in postal survey (standard questionnaire included questions on anthropometric data, BP, physical activity (PA), and smoking). In 98 mothers and 38 fathers of adolescents with hypercholesterolemia (HCH), lipid profile was assessed. Results. Family association of BP increase, especially for mother‑child line, was observed. Family association of increased body mass index (BMI) was greater for father‑child line. Adolescent girls smoke four‑fold as often as their mothers. In smoking families, adolescents smoke twice as often as in non‑smoking ones. Low PA was preva‑ lent both in adolescents and their parents, especially in girls. The association of increased TCH levels in parents and adolescents, especially in girls, was registered. Conclusion. Data on CHD RF family association point to the need for family‑level examination and preventive intervention, if RF have been identified in at least one family member.